Simplify this expression . 22z – 11z + 13 [?]z + [ ]

Question

Simplify this expression
.
22z – 11z + 13
[?]z + [ ]

in progress 0
Thiên Ân 3 months 2021-08-18T07:04:29+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-18T07:05:44+00:00

    Answer:

    11z+ 13

    Step-by-step explanation:

    22z – 11z = 11z

    11z+ 13

    0
    2021-08-18T07:06:06+00:00

    11z+13
    collect your like terms so 22-11=11
    11+13
    11z+13

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )